The Demonstration and Characterization of Deoxyribonucleases of Streptococci Group A, B, C, G And L - Gudding, Roar (Acta Vet Scand, 1979)
Streptococcus pyogenes, S. agalactiae, S. dysgalactiae, S. equi, S. equisimilis, S. zooepidemicus, Streptococcus group G and L were found to produce deoxyribonucleases (DNases) which were demonstrated using the Toluidine Blue DNA Agar (TDA) described for staphylococcal DNases. The activity of streptococcal DNases increased in the presence of Mg(++) and Ca(++) ions, the pH optimum was about 7.5 and native DNA was the best enzyme substrate. It is consequently recommended to modify the TDA according to these results for the demonstration of streptococcal DNases. All streptococcal DNases, except the DNase of S. zooepidemicus, were found to be heat-stable. Isoelectric focusing was a convenient technique for separation of streptococcal DNases and for estimation of the pI values of the DNases. S. agalactiae and S. dysgalactiae generally exhibited distinct species specific patterns in the isoelectric focusing experiments. The DNases produced by S. pyogenes were serologically related to the DNases of S. dysgalactiae and Streptococcus group G. A similar relationship was demonstrated between the DNases produced by S. equisimilis and Streptococcus group L.